Dinamika Ovarium Selama Siklus Estrus pada Domba Garut (OVARIAN DYNAMIC DURING THE ESTROUS CYCLE IN GARUT EWES) - Gunawan, Satya; Yusuf, Tuty Laswardi; Setiadi, Mohamad Agus; Boediono, Arief; Herman, Rachmat; ., Amrozi (Jurnal Veteriner, 2013)
Ovarian dynamics in the garut ewes had never been studied continuously by using ultrasonography.The aim of this study was to observe development of the follicles and corpus luteums in the estrous cyclein the garut ewes. Garut ewes (n=6) with body weight 30.00±4.05 kg which had normal estrous cycle wereused in this study. All ewes were synchronized by using CIDR-G implantation for 14 days. Ovulation of thedominant follicle, development of the follicle waves and corpus luteum were observed continuously everyday during the estrous cycle after CIDR-G removal. The number of small (2-3 mm in diameter), medium (4-5 mm in diameter) and large (>5 mm in diameter) follicles were aligned during the estrous cycle. Follicleand corpus luteum diameters were measured by using built in caliper in the ultrasound. The resultsshowed 1) the average length of estrous cycle was 19,2±0,8 days; 2) ovarian follicle growth occurred inthree waves during the estrous cycle; 3) the number of preovulatory follicles were 1-2 follicles; 4) theaverage maximum diameters of preovulatory follicle was 7.5±0.5 mm; 5) the average maximum diametersof corpus luteum was 7.3±0.4 mm. In conclusion, the estrous cycle in garut ewes was 18-20 days with 3follicular waves.
Keywords: estrous cycle, garut ewes, follicle waves, preovulatory follicle, ultrasonography